Factors affecting piglet mortality during the first 24 h after the onset of parturition in large litters: effects of farrowing housing on behaviour of postpartum sows. (16th October 2018) - Yun, J.; Han, T.; Björkman, S.; Nystén, M.; Hasan, S.; Valros, A.; Oliviero, C.; Kim, Y.; Peltoniemi, O.
Abstract : The present study aimed to identify the factors that affect immediate (within 24 h after farrowing onset) postnatal piglet mortality in litters with hyperprolific sows, and investigate their associations with behaviour of postpartum sows in two different farrowing housing systems. A total of 30 sows were housed in: (1) CRATE ( n =15): the farrowing crate closed (0.80×2.20 m) within a pen (2.50×1.70 m), and (2) OPEN ( n =15): the farrowing crate open (0.80×2.20×1.80 m) within a pen (2.50×2.40 m) with a provision of 20 ls of hay in a rack. A total of 518 live born piglets, produced from the 30 sows, were used for data analyses during the first 24 h after the onset of parturition (T24). Behavioural observations of the sows were assessed via video analyses during T24. Total and crushed piglet mortality rates were higher in OPEN compared with CRATE ( P <0.01, for both). During T24, the OPEN sows tended to show higher frequency of postural changes ( P =0.07) and duration of standing ( P =0.10), and showed higher frequencies of bar-biting ( P <0.05) and piglet trapping ( P <0.01), when compared with the CRATE sows. During T24, the mortality rates caused by crushing were correlated with the piglet trapping event ( r =0.93, P <0.0001), postural changes ( r =0.37, P <0.01), duration of standing ( r =0.32, P <0.01) and frequency of bar-biting behaviour ( r =0.51, P <0.01) of the sows ( n =30). In conclusion, immediate postnatal piglet mortality, mainly due to crushing, may be associated with potential increases in frequency of postural changes, duration of standing and incidence of piglet trapping in postpartum sows in the open crate system with large litters.